Stock Information System for All Smartphone Brands Using Barcode - Wini Istya Sari Lubis; Rakhmat Kurniawan (Indonesian Journal of Data Science, IoT, Machine Learning and Informatics, 2025)
In the era of globalization, rapid development in technology that brings convenience and speed in completing human tasks. A barcode is a collection of optical data that is read by a machine. In fact, this barcode collects data in width (lines) and parallel line spacing and can be referred to as a linear or 1D (1-dimensional) barcode or symbology. Stock reports on purchases and sales of a period are useful for helping employees to assess the amount of inequality in purchasing flows, monitor stock/inventory of goods, and provide reports, both purchase reports, sales reports, and stock condition reports. ALL BRAND SMARTPHONE is a company engaged in the sale of electronic equipment. The process of checking stock at ALL BRAND SMARTPHONE has not implemented a barcode application, but is only done by checking stock manually by conducting manual checks between incoming and outgoing goods, then the final stock of goods will be calculated. Manual calculations or checks allow errors to occur in the creation or input of data. The purpose of designing this inventory information system is to be able to build a web-based inventory system that is expected to minimize errors or manipulation of inventory data using barcodes. And assist companies and employees in managing incoming goods data and outgoing goods data. The research method used involves data collection through observation, interviews, and literature studies, system development with a waterfall methodology approach.